Confidence amongst Multidisciplinary Professionals in Managing Paediatric Rheumatic Disease in Australia. (18th January 2018) - Cassidy, Samuel; Coda, Andrea; West, Kerry; Hendry, Gordon; Grech, Debra; Jones, Julie; Hawke, Fiona; Singh-Grewal, Davinder
Abstract : Objective. Interprofessional collaboration is a crucial component of care for children with rheumatic disease. Interprofessional care, when delivered appropriately, prevents disability and improves long-term prognosis in this vulnerable group. Methods. The aim of this survey was to explore allied health professionals' and nurses' confidence in treating paediatric rheumatology patients. Results. Overall, 117 participants were recruited, 77.9% of participants reported being "not confident at all, " "not confident, " or "neutral" in treating children with rheumatic diseases (RD) despite 65.1% of participants reporting having treated >1 paediatric rheumatology case in the past month. Furthermore, 67.2% of participants felt their undergraduate education in paediatric rheumatology was inadequate. "Journals" or "texts books" were used by 49.3% of participants as their primary source of continuing professional development (CPD) and 39.3% of participants indicated that they did not undertake any CPD related to paediatric rheumatology. Small group and online education were perceived to be potentially of "great benefit" for CPD. Conclusion. This paper highlights allied health professionals' and nurses' perceived inadequacy of their undergraduate education in paediatric RD and their low confidence in recognising and treating RD. Undergraduate and postgraduate education opportunities focusing on interprofessional collaboration should be developed to address this workforce deficiency.